Thermal stability study of grease formulated from industrial waste oil - Nurul Waheeda, Abdu Rahman; Mohd Aizudin, Abd Aziz; Norasiha, Hamid; Nur Suhaila, Anang Japar (Universiti Teknologi PETRONAS, 2020)
This is aimed to investigate the effect of additives on thermal stability of grease formulated with waste transformer oil (WTO). One of the key factors of grease functionality is thermal stability. Grease is unsuitable for high-temperature use if the matrix is unable to withstand high temperature. Addition of additive is able to improve the grease thermal stability. In this work, three types of additives (molybdenum disulphide, fumed silica, and polytetrafluoroethylene) were tested as thermal stability additive. The grease was characterized using ASTM International standards and SKF’s Grease Test Kit. Based on grease characterization, the addition of additive was found slightly affecting the grease properties. Fumed silica was observed able to improve the grease thermal stability by 3.6%.